Professional Competence Development of Library and Information Personnel - Gopinath, M. A. (Journal of Information and Knowledge, 1998)
Presents the need for continuing education of library and information personnel. Identifies the frontier areas for continuing education and competence development. Provides a modular structure of the themes for continuing education.